Clinicopathological evidence of hepatitis B virus infection in the development of gastric adenocarcinoma. Issue 1 (10th September 2019) - Cui, Hongxia; Jin, Yizi; Chen, Fang; Ni, Hengli; Hu, Caihong; Xu, Yudong; Xuan, He; Hu, Duanmin; Deng, Wei; Zhang, Yongsheng; Liu, Yao
Abstract: Gastric cancer (GC) is one of the infection‐related cancers. Helicobacter pylori and Epstein‐Barr virus (EBV) were established risk factors for GC. Recently, there are several reports showing the inconsistent association between hepatitis B virus (HBV) infection and the development of GC. To explore the relationship between HBV infection and the development of GC, we designed a meta‐analysis of previous epidemiological studies, a hospital‐based case‐control study, followed by an immunohistochemistry (IHC) assay of HBV‐exposed GC samples. We found that HBV infection was associated with an increased risk of GC based on the meta‐analysis. No significant association between HBV infection and GC was detected according to our hospital‐based case‐control study. Histological examination showed that the gastric epithelium positive for HBx demonstrated a higher nuclear‐cytoplasmic ratio compared to those HBx‐negative cells. HBx and HBcAg were expressed more in tumors than those in normal counterparts in HBV‐exposed subjects, and PD‐L1 was lower in GC tissues from HBV carriers than those in HBV clearances. In conclusion, HBV infection may contribute to a higher risk for GC based on the meta‐analysis and to the morphological atypia of gastric epithelium by the histological assessment, and GC patients among HBV carriers showed lower expression of PD‐L1 may lose the chance for immune checkpoint blockade therapy. Highlight: HBV infection may contribute to a higher risk for GC based according to the meta‐analysis from several epidemiological studies. Gastric cancer patients among HBV carriers showed lower expression of PD‐L1 and they may lose the chance for immune checkpoint blockade therapy.